Communications under the seas the evolving cable network and its implications - Finn, Bernard S.; Yang, Daqing (Dibner Institute studies in the history of science and technology, 2009)
The technology of undersea communications, from stranded-wire telegraph cables in the 1850s to fiber-optic cables at the end of the twentieth century, and its social, political, and economic impact.